The Implementation of Team Game Tournament (TGT) In Improving Students Listening Skills At MA Manbaul Ulum Al-Ma’arif Kabul In The Academic Year 2024/2025 - Yuliana Yarpiani; Ahmad Syukron Sidik; Karyawan Putraidi; Ria Hendriani (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2025)
The aim of this research is to analyze the implementation of Team Game Tournament (TGT) in improving student’s listening skill. The design of this research is one-group pretest-posttest design type pre-experimental research design. The researcher chose one class as a sample. The number of sample selected was 24 students. The data obtain from multiple choices to fill the blank test. The researcher found that the result of the students’ mean score of pre-test was 79,58 and it was improved to 91,25 in post-test. In addition, the result shows a significant improvement in students’ listening skill after the implementation of Team Game Tournament (TGT). The application of TGT not only enhances listening skill but also increases students’ motivation and participation in the learning process. Therefore, the alternative hypothesis (Ha) is accepted while the null hypothesis is rejected. Based on the result analysis, the researcher occluded that the implementation of TGT can improve students’ listening skill.